Kajian Hukum Islam Terhadap Legalitas Penjualan Bahan Bakar Minyak (BBM) Pom Mini Dengan Menggunakan Nozzle Di Kota Malang - zahra zahadina Zikhaula Toba (Journal of Islamic Business Law, 2018)
This research aims to know the conformity of legislation and Islamic law on the practice of the sale of Fuel (BBM) mini pom using the nozzle. This type of research is empirical legal research with a statute approach and conceptual approach method. The method of primary data collection through a live interview. Results of the study it was concluded as follows: that the sale of fuel oil (FUEL) Mini Pom using the Nozzle already in accordance with the tenets and terms of sale and purchase in the Sharia. Allowed to practise and selling Mini Pom using the FUEL nozzle if it does not break any of the tenets and terms. Sales of fuel oil (FUEL) Mini Pom using the nozzle does not fit according to the applicable law, as it is not in accordance with the standard rules contained in Act No. 2 of 1981 years of Legal Metrology. In article 12 (a) which reads "With Government regulations set of measuring tools, measure out, weigh it and equipment: (a) compulsory measure and measure". In article 20 paragraph (1) reads "legitimate Sign affixed or attached tools measure, measure out, weigh it and equipment is passed on time measure or measure".